Antimicrobial effects of green and roasted beans of Coffee robusta and Coffee arabica on Streptococcus mutans - An in vitro comparative study - Soni Ashok Gupta; Gauri Vidhyadhar Potdar; Kritika Dinesh Jain; Kajal Pravin Jethwa; Vaibhav Pravin Thakkar; Sabita M Ram; Samir Ramkrishna Pachpute (Wolters Kluwer Medknow Publications, 2023)
Introduction: In India, coffee is the third most common beverage consumed after water and tea. Through this study, we have analyzed the antimicrobial properties of coffee extracts by determining their zone of inhibition on blood agar plates in comparison to chlorhexidine which was used as the control. Aim: The study aims at determining the antimicrobial effects of extracts of green and roasted beans of Robusta and Arabica coffee (in vitro). Methodology: The samples were collected from local markets of Coorg and Navi Mumbai. Streptococcus mutans were cultured on blood agar, which was then inoculated with these samples. Antimicrobial properties were determined using the agar well diffusion method. The results were compared with gold standard solution, i.e., 0.2% chlorhexidine solution. Results: The coffee bean extract of Green Robusta showed a more inhibitory effect on S. mutans when compared to Roasted Arabica and Chlorhexidine. The diameter of the zone of inhibition around the extracts of Green Robusta was 22 mm, 22.5 mm, 23.5 mm, and 24 mm of 2 g, 4 g, 10 g, and 20 g, respectively, and that of Roasted Arabica was 11 mm, 12 mm, 13.5 mm, 15 mm of 2 g, 4 g, 10 g, and 20 g, respectively. Conclusion: According to this methodology, Green Robusta has more inhibitory effects than chlorhexidine. Thus in future after more in vivo and in vitro studies, coffee may be used in dental aids such as mouthwashes, dentifrices, dental floss, and chewing gum for its antimicrobial effect.